Body Measurement Technology and Utilisation: Implications for Africa - Otieno , Rose Bujehela (African Journal of Education,Science and Technology (AJEST), 2013)
Anthropometry is fundamental in medicine, ergonomics, clothing, nutrition, fitness and health among other areas. Although utilised worldwide for clothing purposes, body measurement was based on manual and more recently, digital methods mainly in selected countries especially in the West. Current trends focus on new technology including state-of-the-art body scanning and subsequent utilisation and integration of such data in medicine, ergonomics, clothing design, health and fitness. Major national surveys continue to be conducted worldwide, but these are proprietary especially because of the cost implications and funding arrangements. While some measurement of African populations has been conducted, documentation and dissemination of such data is limited, thereby creating an apparent gap in knowledge and its application. The purpose of this paper is to contextualise body measurement in clothing technology and the utilisation of such data in Africa; and to present views from clothing technology perspectives that were collected from specialists and final year university students. Using an interview schedule, data were collected and analysed. Areas for focus were knowledge, educational programmes, usability, availability, new technology and its up-take, research and utilisation in industry. Findings reveal the urgent need for current comprehensive anthropometric data regarding African populations such as the Kenyan one. Poor resources and relevant knowledge, technology cost, poor up-take are reasons for lack of utilisation. To leverage funding, collaboration between governments, educational and research institutions on the one hand and related industry on the other is recommended. Integration of new digital and scanning technologies in body measurement could enhance global competitiveness; with validity and usability of such data across the different disciplines. The importance, context and implications of body measurement technology in clothing in Kenya and Africa are discussed